PERSONAL HYGIENE AND REPRODUCTIVE HEALTH KNOWLEDGE AMONG ADOLESCENTS AT KAMPUNG BELAJAR, SURABAYA - Nuranisah Djunaedi; Yuly Sulistyorini (Universitas Airlangga, 2021)
Health knowledge is fundamental for everyone, including children. This knowledge provides understanding for children in preparation for entering puberty. However, health education which discusses personal hygiene, anemia, puberty, and healthy relationships, as well as reproductive health is still very limited in formal schools. Because of these limitations, children need to get informal education. One of the ways this is done is through health education activities at Kampung Belajar. The research objective was to analyze health knowledge on personal hygiene, anemia, puberty, healthy relationships, and reproductive health taught through health education at Kampung Belajar in Jambangan, Surabaya. This study used secondary data sources obtained from the teaching team at the learning village. The data obtained were the result of evaluating learning activities related to health knowledge. The research subjects were 22 students from grade 1 to 7. The results of this study were 0.031 with p < 0.05. It can be concluded that there was a difference in health knowledge, which included personal hygiene, anemia, puberty, healthy relationships, and reproductive health in the study group after receiving health education provided by the teaching team at Kampung Belajar.